2020
DOI: 10.1007/s00134-020-06211-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of critically ill patients with novel coronavirus infectious disease (COVID-19) in China: a retrospective multicenter study

Abstract: Purpose An ongoing outbreak of coronavirus disease 2019 (COVID-19) emerged in Wuhan since December 2019 and spread globally. However, information about critically ill patients with COVID-19 is still limited. We aimed to describe the clinical characteristics and outcomes of critically ill patients with COVID-19 and figure out the risk factors of mortality. Methods We extracted data retrospectively regarding 733 critically ill adult patients with laboratory-confirmed COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
176
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(195 citation statements)
references
References 28 publications
15
176
2
2
Order By: Relevance
“…In summary, as suggested by Xie et al [1] and confirmed by Table 1, hemodynamic instability is common in COVID-19 ICU patients. However, the hemodynamic phenotype of patients receiving vasopressors remains poorly documented.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…In summary, as suggested by Xie et al [1] and confirmed by Table 1, hemodynamic instability is common in COVID-19 ICU patients. However, the hemodynamic phenotype of patients receiving vasopressors remains poorly documented.…”
supporting
confidence: 61%
“…Indeed, a majority of them mentioned they had to administer vasopressors to ICU patients either frequently (> 50% of the cases) or very frequently (> 75%). Therefore, the rate of patients requiring vasopressor support reported by Xie et al [1] was on the low end of previous findings reported in the literature (Table 1).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…other viral pneumonias (non-COVID- 19)]. We had a high level of completeness of outcome data (with only 3.8% still in acute hospital at database lock), comparing favourably with other reports [28][29][30] and we did not restrict our analyses to select groups. This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The value of laboratory surrogate markers specific for COVID-19 for risk estimation and treatment optimization cannot yet be adequately assessed. [15][16][17][18] Odds Ratio (95 %-KI)…”
Section: Fatality and Risk Factors For Severe Courses Of Covid-19 Pnementioning
confidence: 99%